1995
DOI: 10.1083/jcb.129.3.867
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative signaling by alpha 5 beta 1 and alpha 4 beta 1 integrins regulates metalloproteinase gene expression in fibroblasts adhering to fibronectin.

Abstract: Abstract. Rabbit synovial fibroblasts (RSF) express basal levels of the metalloproteinases (MMP) collagenase, stromelysin-1 and 92-kD gelatinase when plated on intact fibronectin (FN), but elevated levels when plated on either the central RGD-containing cell-binding region of FN (120FN) or antibody against the ot5/~l integrin, suggesting that domains outside 120FN may suppress the induction of MMP (Werb, Z., P. M. Tremble, O. Behrendtsen, E. Crowley, and C. H. Damsky. 1989. J. Cell Biol. 109:877-889). We there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
212
4
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(223 citation statements)
references
References 74 publications
6
212
4
1
Order By: Relevance
“…Fn is a multifunctional protein whose activities are due to functional domains present both in the native ''full-length'' protein 16,17 and its multiple sub-fragments. Indeed, when released by limited proteolysis, these functional domains display specific activities, latent in the native Fn.…”
Section: Discussionmentioning
confidence: 99%
“…Fn is a multifunctional protein whose activities are due to functional domains present both in the native ''full-length'' protein 16,17 and its multiple sub-fragments. Indeed, when released by limited proteolysis, these functional domains display specific activities, latent in the native Fn.…”
Section: Discussionmentioning
confidence: 99%
“…a3b1 integrin was shown to participate in phagocytosis of extracellular matrix (Coopman et al, 1996). a2b1, a3b1, a4b1, and a5b1 integrin were found to be involved in the regulation of matrix metalloprotease expression (Larjava et al, 1993;Huhtala et al, 1995;Riikonen et al, 1995). In addition, activation of a6b1 integrin increased invasiveness of LOX human melanoma cells correlating with a 2 ± 3-fold elevation of extracellular matrix degradation and invadopodial activity (Nakahra et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Third, integrins are necessary for basement membrane penetration, since RGD peptides interfering with ligand binding to certain integrins prevented this process in vitro (Gehlsen et al, 1988). And ®nally, integrins are involved in the regulation of protease expression and their localized activities, as demonstrated in tissue culture experiments (Huhtala et al, 1995;Riikonen et al, 1995;Brooks et al, 1996;Coopman et al, 1996;Nakahara et al, 1996). In vivo changes in the metastatic potential of tumor cells often correlated with changes of the integrin expression pattern.…”
Section: Introductionmentioning
confidence: 99%
“…39 A number of studies have addressed the correlation of MMP expression with invasive ability of malignant tumors. [40][41][42][43] It has been shown that signal transduction through ␤1 integrins induces MMP production 44,45 and activation of MMP proenzymes. 46 Furthermore, activated MMPs can be localized with ␤1 integrins at the focal contacts on the surface of invasive cells.…”
Section: Discussionmentioning
confidence: 99%